The impact of COVID-19 on the environment / Nor Azira Ismail - Ismail, Nor Azira (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
In early 2020, the world has been shocked with the new coronavirus (SARS-CoV2) which has generated an unprecedented impact in most countries of the world. The virus has affected all 213 countries, include countries in Asia, in Europe (mainly in Italy, Spain, France and UK), in Africa and America (mainly in the United States) spread to more than 2 million people, and caused around 130, 000 deaths until categorized as a pandemic by the World Health Organization (World Health Organization, 2020). Currently, there still no viable vaccine and therapy found to stop the virus from spreading except to follow the standard advice which is to avoid close contact with those infected, practise good hygiene and social distancing. In addition, most countries have opted to implement lockdown to stop the spread of COVID-19. This pandemic does not only affect the human health, but also triggers socio-economic and political crises as well as environmental degradation in the infected countries. On the other hand, the lockdown has also created a ground for renewal of the environment, especially with the closure of factories and the reduction of both private and public transportation vehicles used. COVID-19 has increased the air quality in many parts of the world with the lockdown imposed during the pandemic process. This is supported by Chakraborty and Maity (2020), who emphasized that the lockdown has both environmental and economic impact on countries. However, this paper attempt to discuss the impact of COVID-19 to environment in several places around the world conceptually.